ANALISIS JUMLAH LUBANG RESAPAN BIOPORI PADA LAHAN TERBUKA KAMPUS FAKULTAS TEKNIK UNIVERSITAS TEUKU UMAR - Muhammad Ikhsan; Meidia Refiyanni (Universitas Teuku Umar, 2017)
This study aims to determine the number of biopori infiltration holes (LRB) that can increase water absorption into the soil, so as not to become a puddle. This happens because of land use changes that occurred in the campus field Teuku Umar University, including in the Engineering Faculty Teuku Umar University. Changes in land use and reduced open space on the UTU campus are expected to result in shrinking infiltrated rainwater and causing increased surface run-off. Increasing the flow of this surface can cause the existing drainage channel dimensions are not enough anymore so the water is abundant and there are floods inundation. Therefore, in order to avoid flooding this puddle, it is necessary to enlarge the infiltrated rain water, among others, with “Lubang Resapan Biopori” (LRB). The location of the LRB is done in front of the Faculty of Engineering building located on the UTU campus land, the LRB manufacture is done in 3 locations but one of the locations can not be used because of high runoff and puddles, therefore only 2 locations are made LRB manufacture, 3 cylindrical holes are made by digging in the soil using manual drill tool, 10 cm diameter drill bit and 80-100 cm long, and 100 cm LRB spacing, then organic waste. From the results of data analysis, the number of biopori infiltration holes recommended for the UTU Faculty of Engineering area requires as many as 68 LRB. Keywords : LRB, Rainfall, Surface Run-off, Organic waste, Engineering Faculty of UTU